The Role and Regulatory Mechanism of Transcription Factor EB in Health and Diseases - Zhu, Sheng-yu; Yao, Ren-qi; Li, Yu-xuan; Zhao, Peng-yue; Ren, Chao; Du, Xiao-hui; Yao, Yong-ming (Frontiers in Cell and Developmental Biology, 2021)
Transcription factor EB (TFEB) is a member of the microphthalmia-associated transcription factor/transcription factor E (MiTF/TFE) family, and its transcriptional activity is largely determined by subcellular localization. In normal condition, TFEB mainly locates in the cytoplasm with inactivated form, while it is rapidly recruited and transfers to nucleus in response to various cellular stress, such as starvation and lysosomal dysfunction. TFEB plays an essential role in cellular responses via transcriptional regulation of multiple target genes, including the biosynthesis of multiple organelles, autophagic activities, and modulation of immune responses. TFEB is capable of regulating the expression of multiple lysosomal proteins by identifying and combining the coordinating lysosomal expression and regulation (CLEAR) elements. Since lysosomes act as the terminals of autophagy, TFEB also modulates autophagy through lysosomes. While the regulation of autophagy by TFEB is not limited to targeting lysosomes, TFEB is involved in cargo recognition, formation of autophagosomes, and the fusion between autophagosomes and lysosomes. The dysregulation of TFEB activity is confirmed with critical involvement in the pathophysiological process of various diseases, such as the catabolic hyperactivity in tumors, the accumulation of abnormal aggregates in neurodegenerative diseases, and the aberrant host responses in inflammatory diseases. Therefore, TFEB might serve as a potential therapeutic target for the treatment of human diseases, thereby inhibiting TFEB to increase the metabolic stress or chemotherapeutic sensitivity of tumor cells, upregulating TFEB to migrate oxidative stress and promote the clearance of inflammatory substances in inflammatory diseases, and enhancing TFEB activity to reduce the accumulation of pathogenic proteins by increasing lysosomal function in neurodegenerative diseases.